Comparativo químico e físico da aplicação de biofertilizante de serapilheira e pó de basalto na cultura de milho (Zea mays) - Wnuk, Ana Luiza (2018)
The use of biofertilizers has shown great results regarding soil fertility, as well as pest and disease control. This project aimed to compare soil physical and chemical changes after application of different dosages of biofertilizer based on litter and basalt powder on corn crop. The experiment was carried out in open plantation and the culture chosen for the development of the study was made because it is currently one of the most produced cereals in the world and one of the most cultivated foods in Brazil, as well as an energy culture of extreme importance. The objective of this study was to compare changes in soil physical and chemical analyzes after application, being a control. The biofertilizer was prepared exclusively for the application of the study, having two stages of preparation (solid and liquid) with a total duration of 45 days to the end of the production. The application was performed with dosages of 0, 25, 50, 75 and 100% for the 500 millimeters measurement, the remainder being filled with water. Five plants of maize were irrigated with each compound, where each plant received the amount of 500 ml in the irrigation. These occurred in the pre-planting (directly on the soil) and after every five days. The phytotechnical parameter (plant height) was analyzed, and the soil samples collected were 0 - 20 centimeters, and an amount of each plant pit was collected, where the five samples of each dosage value were mixed resulting in single material for analyze. With these samples, physical and chemical analyzes of the soil were carried out.